2018
DOI: 10.1002/gj.3232
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics, origin, and significance of mafic microgranular enclaves in the granitoids from the Bailingshan complex, Eastern Tianshan, NW China

Abstract: The Bailingshan complex is located to the south of the Jueluotage tectonic belt of Eastern Tianshan, consisting of quartz monzodiorite, granodiorite, monzogranite, and granite. Mafic microgranular enclaves (MME) are commonly found in granodiorites and monzogranites and have sharp contacts with the host rocks. Sometimes, the fine veins of the host rocks cut through the enclaves. The MMEs are mainly fine‐grained dioritic rocks, including diorite and pyroxene diorite with igneous textures, and having condensing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The loadings were 0.822, 0.816 and 0.719 for Zn, Cd and Pb, respectively. These three metals are commonly found together in various types of ore deposits [ 43 , 76 ]. The upper reaches of the Heihe River originates in the Qilian Mountains, which is in the Qilian metallogenic belt, one of the six grand metallogenic belts in the Tibetan Plateau.…”
Section: Resultsmentioning
confidence: 99%
“…The loadings were 0.822, 0.816 and 0.719 for Zn, Cd and Pb, respectively. These three metals are commonly found together in various types of ore deposits [ 43 , 76 ]. The upper reaches of the Heihe River originates in the Qilian Mountains, which is in the Qilian metallogenic belt, one of the six grand metallogenic belts in the Tibetan Plateau.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the granitoids in the study area have been considered as a component of the Bailingshan granitic complex (Zhao et al, 2019). Zircon U–Pb dating results have shown that they have emplaced at the age of 317–307 Ma (Chen et al, 2018; Fan et al, 2018; Zhang et al, 2016). Three sets of fault systems, mainly NE‐, E‐W‐, and NW‐trending, are developed in the deposit area (Jia & Zhao, 2017).…”
Section: Deposit Geologymentioning
confidence: 99%
“…Their vestiges typically occur as enclaves (e.g. pillows) and distended syn-plutonic dykes that exhibit visible evidence of magma mingling and limited evidence of mixing, resulting in rocks with intermediate compositions (Collins et al 2000;Chen et al 2018). As the granite solidifies beyond the particle locking threshold (~72-75% solidification, Vigneresse et al 1996), the latest mafic intrusions may be preserved as discrete syn-to late-plutonic dykes ranging from diabase to lamprophyre in composition.…”
Section: Conceptual Model For Coeval Appinite Suite and Granitoid Com...mentioning
confidence: 99%
“…However, most internal domains of batholiths preserve field evidence of interaction between coeval granitoid and mafic magmas, such as the presence of mafic enclaves (e.g. Vernon 1984; Barbarin and Didier 1992;Clarke et al 2000;Chen et al 2018), as well as petrographic and geochemical evidence for processes such as mingling and mixing, which can produce rocks of intermediate compositions (e.g. Chappell 1996;Tate et al 1997;Baxter and Feely 2002;Miller et al 2009;Muir et al 2014).…”
Section: Introductionmentioning
confidence: 99%